Model Pembelajaran Numbered Head Together (NHT) Dalam Meningkatkan Hasil Belajar Tematik Peserta Didik Madrasah Ibtidaiyah - Fatimah, Siti; Syamsudin, Syamsudin (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This research is motivated by the inactivity of students in following the lessons given by the teacher because the teacher only uses the same method in every teaching and learning activity, always uses a monotonous teaching method so that it makes students bored which results in low learning outcomes of students in Elementary School. which is marked by the learning outcomes of students who have not reached the minimum completeness criteria. The purpose of this study was to describe the effect of learning using the Numbered Head Together (NHT) cooperative learning model on thematic learning outcomes. This research uses a qualitative research approach with the type of literature research or literature review (Literature Review or Literature Research), which is research where the object of research is explored through a variety of library information (books, encyclopedias, scientific journals, newspapers, magazines, theses, theses and documents). The data used are 10 primary data from journals and theses, supported by secondary data, namely supporting and complementary references to primary sources. According to the literature review, it was found that learning using the Numbered Head Together (NHT) cooperative model had a positive effect and a significant increase on students' thematic learning outcomes when compared to learning that did not use the Numbered Head Together (NHT) cooperative learning model. As a Elementary School, it really needs varied, interesting and innovative learning because students at Elementary School age are very fast to get bored and very active. This cannot be separated from the role of an educator in the learning outcomes of students in the learning process. Therefore, educators are required to be able to use and develop learning models that are in accordance with the learning process in the school where they teach.